2020
DOI: 10.2351/7.0000066
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research of picosecond laser based edge preparation of cutting tools

Abstract: In this study, using ultrafast lasers of 10 ps pulse duration as a precise and efficient method for cutting edge preparation is researched. Cutting edge preparation is an important step within cutting tool manufacturing, while unprepared sharp cutting edges show low stability, which leads to tool failure by high mechanical and thermal loads during the turning processes [C. F. Wyen, W. Knapp, and K. Wegener, Int. J. Adv. Manuf. Technol. 59, 899–914 (2012)]. The rounding of the edges requires laser manufacturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The authors found that the laser with different wavelengths 532 nm (VIS) and 1064 nm (IR) can be used to round the cut edges, because the accuracy is high. When analysing the mechanical properties of the obtained cutting tools, no change in hardness was observed, and the roughness obtained R a was less than 0.15 µm [30]. Sibalija et al analysed the following parameters: cutting speed, auxiliary gas pressure, and laser power focusing position on the 2 mm thick Nimonic 263 alloy.…”
Section: Synthesis Of Literaturementioning
confidence: 99%
“…The authors found that the laser with different wavelengths 532 nm (VIS) and 1064 nm (IR) can be used to round the cut edges, because the accuracy is high. When analysing the mechanical properties of the obtained cutting tools, no change in hardness was observed, and the roughness obtained R a was less than 0.15 µm [30]. Sibalija et al analysed the following parameters: cutting speed, auxiliary gas pressure, and laser power focusing position on the 2 mm thick Nimonic 263 alloy.…”
Section: Synthesis Of Literaturementioning
confidence: 99%
“…The power and cutting speed of the double laser affect the quality of sapphire cutting. Laser energy is the main energy source in the laser cutting of sapphire [40,41]. The energy of sapphire irradiated per unit of time is determined by the laser power and scanning speed, and laser power has an important impact on cutting quality.…”
Section: Influence Of the Laser Cutting Of Sapphire On The Chipped Ed...mentioning
confidence: 99%
“…Nesse contexto, KANG et al (2020);PETER et al (2020) afirmam que a preparação da aresta de corte, aliada às condições de corte apropriadas, pode influenciar nas forças geradas durante a usinagem e aumentar a resistência ao desgaste das ferramentas, gerando, assim, maior vida e melhor acabamento superficial para a peça usinada. YANG; LIANG; ZHENG (2011) afirmam que a preparação de arestas, por meio do seu arredondamento, tem influência na temperatura de corte e AGIC et al ( 2019) constataram experimentalmente que o arredondamento da aresta de corte exerce influência na vibração durante o processo de corte.…”
Section: Motivaçãounclassified